Senyapan Keraguan Tuturan Narasumber Sujiwo Tejo dalam Tayang Bincang Karni Ilyas Club - Febrianti Dwi Rahayu; Fitri Amilia; Rofiatul Hima (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research aims to describe the duration of the shortest, medium and longest silent silences as well as the form of filled silences in Sujiwo Tejo's speech on the Karni Ilyas Club talk show. The method used in this research is descriptive qualitative. At the data collection stage, this research uses documentation, listening and note-taking techniques. Data analysis in this study used the HBB advanced technique matching method and the agih method with an advanced technique in the form of the lesap technique. The results of this study showed that the shortest silent silence duration was 285 ms when saying Yes // [285] and 297 ms when saying logic // [297]. Silent silences of medium duration were obtained with a duration of 462 ms, 371 ms when saying I use //[462] and screenshoot //[371] and 492 ms when saying there //[492]. Meanwhile, long silent silences have a duration of 3251 ms when saying baseball //[3251], and 3809 ms when saying Pak Karni //[3809]. The form of filled silences in Sujiwo Tejo's speech consists of filled sounds and words.